PEMBELAJARAN MENULIS TEKS BIOGRAFI PADA SISWA SMK KELAS X DENGAN MENGGUNAKAN MODEL THINK TALK WRITE (TTW) BERBANTUAN MEDIA POWTOON - putri, intan noviyanti; sobari, teti; latifah, latifah (IKIP Siliwangi, 2020)
Writing is an activity expressing the thoughts, ideas, and feelings of a person as outlined in written language. This research is motivated by the lack of student interest in writing because students find it difficult to put ideas and ideas into written form. The purpose of this study is to examine the scenario and implementation of learning to write biographical texts in Class X vocational students using the Think Talk Write (TTW) model assisted by Powtoon media, examine the responses of teachers and class X vocational students to learning to write biographical text using the Think Talk Write model (TTW) is assisted by Powtoon media and examines the difficulties experienced by students of Class X vocational Schools in completing assignments to write biographical texts. The method used in this research is descriptive qualitative method by describing the facts in the field. The subjects of this study were SMK students of class X-BDP 1 with a total of 30 students. The learning process lasts for two meetings. The results showed that the results of student implementation were 94.3% and the results of teacher implementation were 98.3%. The response of students getting a percentage of 58.3% was categorized very high and the response results of teachers getting a percentage of 57% were categorized high. In working on biographical text writing problems the difficulties experienced by students in the aspects of using Indonesian Spelling (EBI) and aspects of writing.